(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Thalassemias are the most common heritable blood disorders that represents a major public concern. Poor awareness and lack of knowledge lead to increase number of carrier that is a silent reservoir of the disease. To observe the knowledge and awareness level of parents of thalassemic children about the disease. Materials and methods: This descriptive cross-sectional study was conducted in the Thalassemia ward of Chattogram Maa Shishu-O-General Hospital, Chattogram from July 2013 to June, 2014. Parents of 70 thalassemia patients aged 2-18 years interviewed with a formulated questionnaire based on knowledge status and awareness level of parents towards thalassemia. Data were analyzed by both manually and by SPSS-18. Results: Majority of patients were from rural background (54.3%). Only 8.6% parents were consanguineous parents and majority of them completed only secondary education. 44.3% resolved it as inherited disorder. 52.9% resolved thalassemia cannot be cured. Only 24.3% regarded bone marrow transplantation as a measure of cure. More than half (55.7%) did not know how to prevent thalassemia. Only 37.1% knew about prenatal diagnosis. Carrier status of both father and mother were unknown in majority of patients (80%) and screening of sibs was not done at all in a significant number of patients (51.5%). Only 34.3% wanted to do prenatal diagnosis after conception and 65.7% parents were ready to accept therapeutic abortion if fetus would be diagnosed as thalassemia by prenatal diagnosis. Conclusion: Knowledge level and awareness of parents of thalassemic child regarding the disease is unsatisfactory. To reduce disease burden an awareness program regarding the disease and its prevention covering premarital screening, acceptance of prenatal diagnosis and therapeutic abortion is essential. Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 12-15